GARIS DEPAN KEPEMIMPINAN ADAPTIF TERHADAP RESILIENSI PENDIDIKAN MADRASAH DI ERA DIGITALISASI - Siswadi (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study examines the role of adaptive leadership as a key factor in building the resilience of madrasah education in the era of digitalization using a literature review method. Digitalization presents both opportunities and challenges for madrasahs, particularly regarding technology integration, strengthening teacher capacity, and modernizing institutional management. The findings indicate that adaptive leadership plays a crucial role in transforming the curriculum to be digital literacy-based, enhancing teacher competencies through educational technology training, and implementing efficient and transparent technology-based management. Furthermore, adaptive leadership must also maintain a balance between technological modernization and the preservation of Islamic values so that madrasahs remain relevant, competitive, and rooted in Islamic scholarly traditions.